PENGARUH KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN FORMAL WAJIB PAJAK (Studi Pada KPP Pratama Kendari) - Mustafa, Santiadji; Husin, Husin; Unde, Hajariah (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACTThis research aims to determine the effect between consciousness Taxpayer and Sanctions Tax to Compliance Formal Individual Taxpayer (study on KPP Pratama Kendari).The sample in this research is the individual taxpayer in kendari city totaling 100, methods sampling used in this research is the accidental sampling. The method used in this research is a method of regression analysis multiple linear.These results indicate that the consciousness taxpayers and sanctions tax partially influential positive and significant compliance formal individual taxpayer in kendari city. Simultaneously consciousness taxpayers and sanctions tax to compliance formal individual taxpayer in kendari city influential positive and significant.Â Keywords: Consciousness Taxpayers, Sanctions Tax, Compliance Formal Taxpayer.